2020
DOI: 10.1186/s12913-020-05167-9
|View full text |Cite
|
Sign up to set email alerts
|

Availability, prices, and affordability of selected essential cancer medicines in a middle-income country – the case of Mexico

Abstract: Background: More alternatives have become available for the diagnosis and treatment of cancer in low-and middle-income countries. Because of increasing demands, governments are now facing a problem of limited affordability and availability of essential cancer medicines. Yet, precise information about the access to these medicines is limited, and the methodology is not very well developed. We assessed the availability and affordability of essential cancer medicines in Mexico, and compared their prices against t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…However, the cost of chemotherapy treatment for ALL and retinoblastoma was not affordable. Our result is similar to other studies done in LMICs, which reported that cancer medicines are not affordable [ 26 , 27 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, the cost of chemotherapy treatment for ALL and retinoblastoma was not affordable. Our result is similar to other studies done in LMICs, which reported that cancer medicines are not affordable [ 26 , 27 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…The selection of medicines was based on a previous study (pricing survey) conducted in Mexico in 2017. In that study [48], medicines were selected based on their clinical relevance confirmed by their inclusion in the national formulary, their reimbursement by the public health insurance, and their inclusion in national treatment guidelines. Additionally, acknowledging the dynamics in medicine prices following patent expiry, the current study aimed to focus on on-patent medicines; thus, medicines that were included were under patent protection in Mexico in 2017 (time of the survey).…”
Section: Selection Of Medicinesmentioning
confidence: 99%
“…Prices for Mexico were collected in 2017 through a primary price data survey using the World Health Organization (WHO)/Health Action International (HAI) methodology [48,49]. The WHO/HAI methodology [50] is an internationally acknowledged tool for measuring medicine prices, availability and affordability.…”
Section: Data Sourcesmentioning
confidence: 99%
“…They collected information regarding the cost and availability using a standardized data collection form. At the end of each day, 2 students would enter the data into a designed MS Excel Workbook provided as a part of the WHO/ HAI methodology [14,15] . The items included in the standardized form were as follows: basic information of the facility (hospital name, hospital level, survey date), information of the medicine (medicine in stock in the hospital on the day of data collection, yes or no), dosage, strength, medicine type (OB/LPG), and the retail price at the time of survey ( Table 1) .…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, the price of many anticancer drugs is too expensive, which causes heavy economic burden for cancer patients. Thus, with the aim to precisely assess the affordability, we used the approach proposed by Khatib and Sarwar [18,19] : if the total expenditure of medicine in 30 days accounted for 20% or less of the minimum family monthly income, it was regarded as affordable [15] . The calculation formula was :…”
Section: Affordabilitymentioning
confidence: 99%